Conventional and Islamic banking: perspectives from Malaysian Islamic bank managers. (24th March 2015) - Rod, Michel; ALHussan, Fawaz Baddar; Beal, Tim
This paper attempts to provide a comprehensive review of the Islamic banking extant literature from a Malaysian perspective. There is no novel theoretical perspective; rather, the contribution that this paper makes is to simply illustrate and summarise the range of research being conducted on Islamic banking in a country known for its 'pioneering' role in growing Islamic banking and financing. Hence, this paper provides a comprehensive review of the Islamic banking literature within the Malaysian context before briefly illustrating perspectives of a number of Islamic banking managers in Malaysia. Three themes emerge from interviews with these managers: 1) factor influencing the choice of Islamic versus conventional banking/products; 2) the influence of the Malaysian context; and 3) the issue of Shariah–compliance.